PTK6 inhibition promotes apoptosis of Lapatinib-resistant Her2+ breast cancer cells by inducing Bim. Issue 1 (December 2015) - Park, Sun; Ito, Koichi; Olcott, William; Katsyv, Igor; Halstead-Nussloch, Gwyneth; Irie, Hanna
Abstract Introduction Protein tyrosine kinase 6 (PTK6) is a non-receptor tyrosine kinase that is highly expressed in Human Epidermal Growth Factor 2+ (Her2+ ) breast cancers. Overexpression of PTK6 enhances anchorage-independent survival, proliferation, and migration of breast cancer cells. We hypothesized that PTK6 inhibition is an effective strategy to inhibit growth and survival of Her2+ breast cancer cells, including those that are relatively resistant to Lapatinib, a targeted therapy for Her2+ breast cancer, either intrinsically or acquired after continuous drug exposure. Methods To determine the effects of PTK6 inhibition on Lapatinib-resistant Her2+ breast cancer cell lines (UACC893R1 and MDA-MB-453), we used short hairpin ribonucleic acid (shRNA) vectors to downregulate PTK6 expression. We determined the effects of PTK6 downregulation on growth and survival in vitro and in vivo, as well as the mechanisms responsible for these effects. Results Lapatinib treatment of "sensitive" Her2+ cells induces apoptotic cell death and enhances transcript and protein levels of Bim, a pro-apoptotic Bcl2 family member. In contrast, treatment of relatively "resistant" Her2+ cells fails to induce Bim or enhance levels of cleaved, poly-ADP ribose polymerase (PARP). Downregulation of PTK6 expression in these "resistant" cells enhances Bim expression, resulting in apoptotic cell death. PTK6 downregulation impairs growth of these cells in in vitro 3-D MatrigelTM cultures, and also inhibits growth of Her2+ primary tumor xenografts. Bim expression is critical for apoptosis induced by PTK6 downregulation, as co-expression of Bim shRNA rescued these cells from PTK6 shRNA-induced death. The regulation of Bim by PTK6 is not via changes in Erk/MAPK or Akt signaling, two pathways known to regulate Bim expression. Rather, PTK6 downregulation activates p38, and pharmacological inhibition of p38 activity prevents PTK6 shRNA-induced Bim expression and partially rescues cells from apoptosis. Conclusions PTK6 downregulation induces apoptosis of Lapatinib-resistant Her2+ breast cancer cells by enhancing Bim expression via p38 activation. As Bim expression is a critical biomarker for response to many targeted therapies, PTK6 inhibition may offer a therapeutic approach to treating patients with Her2 targeted therapy-resistant breast cancers.